Odpowiedzi

2009-11-03T00:10:18+01:00
Tg alfa =9/4
tg alfa = y/x czyli y =9, x= 4
r^2 = x^2 + y^2 = 4^2 +9^2 =16 + 81 = 97
r = pierw. kw. z 97
sin alfa = y/r = 9/ pierw. kw. z 97
cos alfa = x/r = 4/ pierw. kw. z 97
ctg alfa =x/y = 4/ 9
2009-11-03T00:27:32+01:00
Tgα=9/4 to ctgα=1:9/4, ctgα=4/9
Sinα/cosα=tgα i sin²α+cos²α=1
sinα=cosαxtgα podstawiamy: sinα=9/4 cosα
Podstawiamy do jedynki trygonometrycznej
(9/4 cosα)²+cos²α=1
81/16 cos²α + cos²α=1
97/16 cos²α=1
cos²α=16/97
cosα=4/√97
sin²α +cos²α=1
sin²α= 1-16/97
sin²α=81/97
sinα=9/√97